2013
DOI: 10.1016/j.febslet.2013.04.048
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori secretes the chaperonin GroEL (HSP60), which binds iron

Abstract: Helicobacter pylori is a bacterium that can use multiple iron sources. However, it is unknown whether this bacterium secretes molecules such as siderophores or haemophores to scavenge iron. Here, we report the first secreted iron-binding protein of H. pylori, which we purified by haem-affinity chromatography. Mass spectrometry analysis revealed its identity as chaperonin (HpGroEL). When we compared HpGroEL with EcGroEL from Escherichia coli, they were homologous, showing 60% similarity. Additionally, purified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…Candidate vaccine studies in rodents have demonstrated that anti‐Catalase antibodies protect against H. pylori infection . The molecular chaperone GroEL is required for the proper folding of extracellular proteins and also binds iron, an essential element for the bacterial infective process …”
Section: Discussionmentioning
confidence: 99%
“…Candidate vaccine studies in rodents have demonstrated that anti‐Catalase antibodies protect against H. pylori infection . The molecular chaperone GroEL is required for the proper folding of extracellular proteins and also binds iron, an essential element for the bacterial infective process …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the co‐chaperonin XnGroES was not found in the OMVs, suggesting a specific export pathway for XnGroEL. How XnGroEL is secreted is not known, but GroEL secretion was previously observed in other bacteria including Helicobacter pylori and Bacillus subtilis (Yang et al ., ; Gonzales‐Lopez et al ., ). The purified XnGroEL was insecticidal to larvae of the cotton bollworm Helicoverpa armigera after oral administration (Joshi et al ., ).…”
Section: Groel As An Important Virulence Factor Of Entomopathogenic Bmentioning
confidence: 97%
“…Antibody responses against hsp60 Hp (Gonzalez-Lopez et al, 2013) were tested by western immunoblotting, as previously described with slight modifications (Bogdanos et al, 2004, Koutsoumpas et al, 2009 …”
Section: Anti-hsp60 Hp Antibody Testing By Immunoblottingmentioning
confidence: 99%
“…Antibody responses to Hp-specific hsp60 (Gonzalez-Lopez et al, 2013) has not been studied in great detail in MS. In the present study, we assessed such antibody reactivities in patients with RRMS and SPMS.…”
Section: Introductionmentioning
confidence: 99%